Informal employment in transition countries: empirical evidence and research challenges - Lehmann, Hartmut (Bonn, 2014)
"Even though informal employment is wide-spread in transition economies the literature on this phenomenon in the region is rather scarce. For policy makers it is important to know the incidence and the determinants of informal employment. In the first part of the paper we demonstrate that its incidence and to a lesser degree its determinants depend on the definition used. We then discuss studies that attempt to test for labor market segmentation in transition economies along the formal-informal divide. The presented results are inconclusive and we come to the conclusion that more work needs to be done before we can make definitive statements about whether labor markets are integrated or segmented in transition economies. Last but not least we introduce a new research area that links risk preferences and selection into labor market states. We show that if individuals have a choice, relatively risk loving workers have an increased likelihood to choose informal employment and self-employment."